Comparison of The Frequency of Necrotizing Enterocolitis with or Without Probiotics Use in Preterm Neonates - Khan, Erum Saleem; Asad Ur Rehman; Naseem, Shabnam; Wahab, Fakhra (Indus Journal of Bioscience Research, 2025)
Background: Necrotizing enterocolitis (NEC) is a gastrointestinal tract medical emergency among premature neonates, notoriously inducing severe morbidity as well as death. Preventive strategies have a central role, particularly in low-income nations. Despite potential with using probiotics in reducing NEC frequency, benefit in selective groups and settings is under researched. Objective: To compare the frequency of necrotizing enterocolitis with or without probiotics use in preterm neonates. Study Design: Randomized controlled trial. Duration and Place of Study: The study was conducted from August 2024 to January 2025 at the Department of Obstetrics and Gynecology, CMH Rawalakot. Methodology: A total of 128 preterm neonates (<37 weeks gestation and <1500 g birth weight) were randomly assigned to two equal groups. Group A received oral Bacillus clausii every 8 hours for 14 days, while Group B received a placebo. NEC was diagnosed based on clinical and radiological findings. Results: Group A showed significantly lower NEC incidence (1.6%) compared to Group B (17.2%) (p=0.003). Stratified analysis revealed consistent protective effects across various subgroups, with a particularly significant reduction among male neonates (2.4% vs. 21.6%, p=0.029). Conclusion: Probiotic supplementation with Bacillus clausii markedly reduces the incidence of necrotizing enterocolitis in preterm neonates.